Research of the range of medication for pulmonary hypertension pharmacotherapy in adults in the pharmaceutical market of Ukraine - A. V. Kabachna; I. S. Datsenko; V. S. Hulpa (The State Expert Center of the Ministry of Health of Ukraine, 2021)
Pulmonary hypertension (PH) is a group of rare diseases, malignant in nature, without optimal treatment quickly lead to death. Such patients usually require expensive, continuous and lifelong treatment. Therefore, the study of the assortment structure of drugs used for the treatment of drugs in adults in the domestic market of medicines (drugs) is very relevant. The aim of the study was to analyze the range of drugs for the pharmacotherapy of drugs in the modern pharmaceutical market of Ukraine. The object of the study was information on drugs registered in Ukraine, which are included in the protocol of treatment of patients with PH. In the process of research, system-review, graphic, documentary and marketing research methods were used. The result of the study showed that in the pharmaceutical market of Ukraine there are no drugs based on INN Epoprostenolum, Treprostinil, Beraprostum, Selexipagum, Macitentan, Tadalafilum, Vardenafilum, recommended by the Adapted clinical guidelines for the treatment of adult patients with PH and Unified clinical protocol of emergency, primary, secondary (specialized) and tertiary (hypersensitivity) medical care «Pulmonary hypertension in adults». Simultaneously INN Rivaroxabanum, Apixabanum, Dabigatranum etaxilatum, Iloprostum, Torasemide, Bosentanum, Ambrisentanum, Riociguat are included in the Unified clinical protocol of emergency, primary, secondary (specialized) and tertiary (hypersensitivity) medical care «Pulmonary hypertension in adults» and tertiary (hypersensitivity) Ukraine, however, are not included in the National List of Essential Medicines, which legally limits the possibility of their purchase by health care institutions for budget funds, but only centrally by the Ministry of Health of Ukraine. The structure of drugs for the treatment of PH in adults according to the ATX classification indicates that the largest share have groups С03С - Diuretics - 36.47%, С08С - Selective calcium antagonists with a predominant effect on blood vessels - 32.94%. The import dependence of the pharmaceutical market of medication for PH treatment is relatively high and constitutes about 60% of the number of trade names of medication for PH pharmacotherapy that needs research in the directions of its expansion through import substitution and legislative settlement of questions of improving the accessibility of this medication group.